Wheat-Thinopyrum Substitution Lines Imprint Compensation Both From Recipients and Donors - Lyu, Zhongfan; Hao, Yongchao; Chen, Liyang; Xu, Shoushen; Wang, Hongjin; Li, Mengyao; Ge, Wenyang; Hou, Bingqian; Cheng, Xinxin; Li, Xuefeng; Che, Naixiu; Zhen, Tianyue; et al. (Frontiers in Plant Science, 2022)
Even frequently used in wheat breeding, we still have an insufficient understanding of the biology of the products via distant hybridization. In this study, a transcriptomic analysis was performed for six Triticum aestivum-Thinopyrum elongatum substitution lines in comparison with the host plants. All the six disomic substitution lines showed much stronger “transcriptomic-shock” occurred on alien genomes with 57.43–69.22% genes changed expression level but less on the recipient genome (2.19–8.97%). Genome-wide suppression of alien genes along chromosomes was observed with a high proportion of downregulated genes (39.69–48.21%). Oppositely, the wheat recipient showed genome-wide compensation with more upregulated genes, occurring on all chromosomes but not limited to the homeologous groups. Moreover, strong co-upregulation of the orthologs between wheat and Thinopyrum sub-genomes was enriched in photosynthesis with predicted chloroplastic localization, which indicates that the compensation happened not only on wheat host genomes but also on alien genomes.